IMPLEMENTASI METODE DRILL DALAM MENINGKATKAN HAFALAN KOSAKATA BAHASA ARAB PADA PROGRAM INTENSIFIKASI BAHASA ASING (PIBA) UIN ALAUDDIN MAKASSAR - Baso Hilmy (Pascasarjana IAIN Sorong, 2025)
This study aims to determine the application of the drill method in improving Arabic vocabulary memorization of public school alumni students in the Foreign Language Intensification Program (PIBA) UIN Alauddin Makassar. This drill method prioritizes repeated practice which is believed to strengthen memory and improve the language skills of public school alumni students, especially in the aspect of Arabic vocabulary. This study uses a descriptive qualitative approach with the subject of the Arabic Language PIBA teacher and the object of public school alumni students in the practice of using the drill method during the learning process of the odd semester of the 2025/2026 academic year. The results of the interviews showed a number of significant positive impacts on the development of students' language skills. There was a clear improvement in terms of vocabulary retention more easily and accurately in various contexts. Students were not only able to memorize, but also able to compose and pronounce sentences in Arabic more fluently. This proves that repeated practice can strengthen students' long-term memory of the target language, in line with the principles of language acquisition that emphasize repeated practice for mastery. This drill method is very helpful, especially in the context of Arabic learning where students are required to memorize and become familiar with the material or vocabulary.